COVID-19 vaccine website accessibility dashboard. Issue 3 (July 2022) - Jo, Grace; Habib, Daniel; Varadaraj, Varshini; Smith, Jared; Epstein, Sabrina; Zhu, Jiafeng; Yenokyan, Gayane; Ayers, Kara; Swenor, Bonnielin K.
Abstract: Background: The COVID-19 pandemic has exacerbated historical inequities for people with disabilities including barriers in accessing online information and healthcare appointment websites. These barriers were brought to the foreground during the vaccine rollout and registration process. Objective: This cross-sectional study aimed to examine accessibility of U.S. state and territory COVID-19 information and registration centralized websites. Methods: The Johns Hopkins Disability Health Research Center created a COVID-19 Vaccine Dashboard compiling COVID-19 information and vaccine registration web pages from 56 states and territories in the United States (U.S.) reviewed between March 30 through April 5, 2021 and analyzed accessibility using WAVE Web Accessibility Evaluation Tool (WAVE). WAVE identifies website accessibility barriers, including insufficient contrast, alternative text, unlabeled buttons, total number of errors, and error density. Web pages were ranked and grouped into three groups by number of errors, creating comparisons between states on accessibility barriers for people with disabilities. Results: All 56 U.S states and territories had COVID-19 information web pages and 29 states had centralized state vaccine registration web pages. Total errors, error density, and alert data were utilized to generate accessibility scores for each web page, the median score was 259 (range = 14 to 536 and IQR = 237) for information pages, and 146 (range = 10 to 281 and IQR = 105) for registration pages. Conclusions: These results highlight barriers people with disabilities may encounter when accessing information and registering for the COVID-19 vaccine, which underscore inequities in the pandemic response for the disability community and elevate the need to prioritize accessibility of public health information.